Responsabilidad profesional del odontólogo frente a la sospecha de maltrato infantil: revisión sistemática de la evidencia clínica, ética y jurídica - Brayan Santiago1 Escobar-Hernández; Pablo Sacaquirín-Zhunio; Ramón Esteban Peñafiel-Maldonado; María Eugenia Mogrovejo Avila; Viviana León-Rodríguez; Miriam Fernanda Ortega López (Salud Medicina e Innovación Journal, 2026)
Introduction: Child maltreatment often causes injuries to the head, neck, and oral cavity, placing dentists in a position to detect possible cases during clinical care. Evidence on their legal responsibilities remains dispersed across bioethics, forensic dentistry, and oral healthcare. Objective: To synthesize the available scientific evidence on dentists’ legal responsibilities in suspected cases of child maltreatment, with emphasis on professional duties and the legal consequences of acting or failing to act. Methods: A systematic review was conducted in accordance with the PRISMA 2020 Statement. PubMed, Scopus, and ProQuest were searched using strategies based on MeSH terms, DeCS descriptors, and free-text keywords. Two reviewers independently selected the studies using Rayyan. Results: Of the 78 records identified, 11 studies met the eligibility criteria. The evidence was organized into three thematic domains: identification of child maltreatment, dentists’ ethical and legal obligations, and barriers to professional action. The studies consistently described a duty to identify and report suspected maltreatment. However, a gap remained between clinical suspicion and formal reporting. Diagnostic uncertainty and insufficient professional training were the most common explanations. Conclusions: Dentists’ professional responsibilities include clinical care and a diligent response that protects the best interests of the child. Reducing the gap between clinical suspicion and timely activation of child protection mechanisms requires stronger legal education, clear institutional protocols, and interinstitutional collaboration.